Roles of Wnt8a during formation and patterning of the mouse inner ear - Vendrell, Victor; Vázquez-Echeverría, Citlali; López-Hernández, Iris; Alonso, Beatriz Durán; Martinez, Salvador; Pujades, Cristina; Schimmang, Thomas (Mechanisms of development, 2013)
► Loss of Fgf3 leads to absence of Wnt8a expression during murine inner ear formation. ► Wnt8a mouse mutants show no defects during inner ear development. ► Double mutants for Wnt8a and Fgf3 show reduced expression of Fgf15. ► Double mutants for Wnt1 and Wnt8a show defects during dorsal morphogenesis of the inner ear. Fgf and Wnt signalling have been shown to be required for formation of the otic placode in vertebrates. Whereas several Fgfs including Fgf3, Fgf8 and Fgf10 have been shown to participate during early placode induction, Wnt signalling is required for specification and maintenance of the otic placode, and dorsal patterning of the otic vesicle. However, the requirement for specific members of the Wnt gene family for otic placode and vesicle formation and their potential interaction with Fgf signalling has been poorly defined. Due to its spatiotemporal expression during placode formation in the hindbrain Wnt8a has been postulated as a potential candidate for its specification. Here we have examined the role of Wnt8a during formation of the otic placode and vesicle in mouse embryos. Wnt8a expression depends on the presence of Fgf3 indicating a serial regulation between Fgf and Wnt signalling during otic placode induction and specification. Wnt8a by itself however is neither essential for placode specification nor redundantly required together with Fgfs for otic placode and vesicle formation. Interestingly however, Wnt8a and Fgf3 are redundantly required for expression of Fgf15 in the hindbrain indicating additional reciprocal interactions between Fgf and Wnt signalling. Further reduction of Wnt signalling by the inactivation of Wnt1 in a Wnt8a mutant background revealed a redundant requirement for both genes during morphogenesis of the dorsal portion of the otic vesicle.